2022
DOI: 10.3389/fnut.2022.816836
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei Strain Shirota Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice by Increasing Taurine-Conjugated Bile Acids and Inhibiting NF-κB Signaling via Stabilization of IκBα

Abstract: Inflammatory bowel disease (IBD) is a chronic progressive intestinal inflammatory disease, characterized by an altered gut microbiota composition and accompanying alterations in circulatory bile acids. Increasing evidence supports the beneficial effect of probiotics intake on health. Introduction of probiotics to the intestines can modulate gut microbiota composition and in turn regulate the host immune system and modify the inflammatory response. Probiotics can also improve intestinal barrier function and exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
(61 reference statements)
2
13
0
Order By: Relevance
“…Based on our previous research proposing that tacrolimus plus gut microbiota achieved an increased allograft survival rate ( Zhang et al., 2018 ), this study confirmed that the combination of tacrolimus and Lactobacillus strains played a positive role in colitis. Since we observed that the colonic contents were inadequate for the detection of two-omics, especially in the condition of colitis, the cecal content was used following the protocol as previous studies ( Wong et al., 2022 ). There are certain limitations to do this since the most representative alterations in the gut microbiome are in the area where inflammation occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous research proposing that tacrolimus plus gut microbiota achieved an increased allograft survival rate ( Zhang et al., 2018 ), this study confirmed that the combination of tacrolimus and Lactobacillus strains played a positive role in colitis. Since we observed that the colonic contents were inadequate for the detection of two-omics, especially in the condition of colitis, the cecal content was used following the protocol as previous studies ( Wong et al., 2022 ). There are certain limitations to do this since the most representative alterations in the gut microbiome are in the area where inflammation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, an improved composition of the gut microbiome and bile acid metabolism might help explain the mechanism of amelioration after combination therapy. A recent study has shown that one strain from Lactobacillus casei ameliorated DSS-induced colitis in mice by increasing taurine-conjugated bile acids, and the activation of FXR by the increased TCDCA might exhibit anti-inflammatory effects ( Wong et al., 2022 ). This possibly resulted from the activation of FXR shifting the polarization of macrophages toward the anti-inflammatory M2 phenotype, which promoted IL-10 secretion and inhibited IFN-γ production ( Fiorucci et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics can restore abnormal BA metabolism in IBD patients. The administration of Shirota strain of Lactobacillus casei could significantly ameliorate the severity of DSS-induced colitis by restoring the composition of the gut microbiota and circulating bile acid profiles in colitic mice [ 102 ].…”
Section: Probiotics and Ibdmentioning
confidence: 99%
“…et al. showed that increasing the amount of taurine conjugated bile acids through Lactobacillus case strain Shirota (LcS) mediated increases led to improvement in DSS induced colitis ( 111 ). Specifically, improvement in colon length, improvement in histological architecture, and decreases in CD45 expression in the colons of these mice as compared to untreated mice with DSS colitis.…”
Section: Bile Acids As Therapeutic Agents For Intestinal Inflammationmentioning
confidence: 99%